Composição de contratos de afretamento para renovação de frota de embarcações de apoio marítimo: um método de otimização sob incertezas - Souza, Marcelo Oliveira de (Universidade do Vale do Rio dos Sinos, 2019)
This thesis develops a method for analysis and decision support in the process of fleet renewal of chartered vessels, dedicated to the supply of maritime units (MU's) for oil and natural gas exploration and production. The purpose of the method is to determine the most appropriate composition of charter contracts, considering the uncertainties related to demand and chartering prices, in order to maintain complete fulfillment of MU's needs at the lowest possible cost. To perform this objective a problem analysis and solution method was developed, which involves: investigation of available information, problem modeling, study and implementation of optimization strategies under uncertainties, value analysis and results evaluation. The method was applied to a real problem of a large oil and gas company operating in Brazil, where different demand and price scenarios were evaluated to arrive at the optimal chartering plan. Results analysis shows that optimization techniques that simultaneously consider uncertainties in the problem mathematical modeling are the most appropriate for solving optimization problems under uncertainties.
Keywords: Afretamento marítimo; Otimização sob incertezas; Programação linear inteira; Programação estocástica; Análise de valor; Offshore logistics; Maritime chartering; Optimization under uncertainties; Integer linear programming; Stochastic linear programming; Value analysis; ACCNPQ::Engenharias::Engenharia de Produção